Layanan Bimbingan Kelompok Melalui Permainan Tradisional Untuk Mempererat Hubungan Pertemanan Siswa di SMP Negeri 2 Kota Jambi - Anggi Rizka Putri; Nelyahardi Nelyahardi; Hera Wahyuni (Journal on Education, 2023)
This study aims to analyze the level of friendship that occurred in class VII SMP Negeri 2 Jambi City before and after being given treatment through traditional games, to see whether there were differences between the control group and the experimental group before and after being given treatment through traditional games in class VII SMP Negeri 2 City of Jambi. This type of research is quantitative with an experimental method using a quasi-experimental designnonequivalent control group design, using a data collection technique in the form of a questionnaire instrument. The determination of the questionnaire instrument uses validity and reliability tests. The data analysis test was carried out, namely the normality test and homogeneity test which was carried out with the help of the SPSS 24 program. The hypothesis test was carried out by the t-test with a sample of 20 people taken by the purposive sampling. The results of this study showed differences in student friendships with an average score of 19.2 for the experimental class, and 15.2 for the control class. This coincides with the value of the different test results (t), from the calculations obtained Tcountthat is as big as Ttablewith a result of 2,101. So when included in the hypothesis formula Tcount> Ttable, until HO rejected and Ha accepted. These results indicate that using traditional games can strengthen student friendships.